Mind your own business - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Across the world, a civil service job pays well and is secure. Not bad if you can get it, with competitive entry to it by hordes of applicants.